(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Accurate calibration of the harvester head relies on accurate manual log measurements. According to the recommended calibration procedures as proposed by the harvester manufacturer the differences between the volume measurements from harvester measurement system and the caliper-and-tape system must be within ± 3% and harvester diameter measurements within ± 6mm of manual measurements in 80% cases. Requirements in Latvia stipulate that total volume measurement accuracy levels must be within ± 5% of actual volume if veneer or birch logs are being harvested, ± 3% if saw logs are being harvested and ± 10% if pulp wood or fire wood are being harvested. The purpose of this study is to assess the impact of harvester calibration on the accuracy of birch veneer logs measurements by Measuring Diameter in Short Intervals using electronic 3D systems when different double bark volume determination algorithm are used in harvester and stacionar measurement system. The research was carried out in December 2016 in the region Latgale in Latvia. The wood felling area was chosen - Mercurialiosa mel. For volume estimation the sequent measurement equipment were applied: harvester Ponsse ERGO 8W, harvester information system Opti 4G and electronic 3D scanner system Elmes 3600. The research is a continuation to the work done in the project „Harmonisation of piece-by-piece measurement methods of roundwood approved by Standard LVS 82:2003 „Apaļo kokmateriālu uzmērīšana” [6], the project “Harmonization of piece-by-piece measurement methods in all stages of roundwood manufacturing processes” [7] and the project "Investigation and evaluation of the methodology of determination of solid volume according to the stacked volume on roadside and in forwarder loads for logistics purposes in LATVIA" [8].